The Effect of Green Accounting Implementation on Improving the Environmental Performance of Mining and Energy Companies in Indonesia - Wahyuni Wahyuni; Inten Meutia; Syamsurijal Syamsurijal (Binus Business Review, 2019)
The research explored implementation of green accounting that was taken from the green accounting concept containing quantitative and qualitative information reported by the company. The observation period of this research was three years from 2014 to 2016. The object of this research was the mining and energy companies registered in the Global Reporting Initiative (GRI) database in Indonesia. The data used were secondary data obtained from sustainability reporting with the GRI-G4 report type. Data analysis was using panel data regression with a random effect model approach. The results show that the implementation of green accounting in the form of recycled materials, renewable energy, and green cost allocation has a positive and significant effect on improving environmental performance. Conversely, Corporate Social Responsibility (CSR) fund allocations do not affect environmental performance.